The moderating role of gender in shaping entrepreneurial intentions: implications for vocational guidance - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (Springer, 2014)
This study examines the relationships among attitude toward entrepreneurship, entrepreneurial self-efficacy, subjective norms, social valuation of entrepreneurship, and entrepreneurial intentions and how gender affects the relationships. Structural equation modeling was used to analyze the responses obtained from 719 Malaysian students across five universities. The results suggest gender significantly moderates the relationship between students’ entrepreneurial intention and its antecedents. While entrepreneurial attitude and self-efficacy had greater effects on males’ intentions to become entrepreneurs, entrepreneurial attitude and subjective norms had stronger impact on females’ entrepreneurial intentions. Furthermore, social valuation of entrepreneurship had an indirect relationship with entrepreneurial intention through self-efficacy and subjective norms.